Static And Dynamic Analysis of Tall Structure with The Help of Staad.Pro - Sameer Soni; Prof. Vinay Kumar Singh Chandrakar (International Journal of Scientific Research in Civil Engineering, 2022)
Tall buildings are susceptible to dynamic horizontal loads such as wind and earthquakes. These horizontal forces cause important stresses, displacements and vibrations due to the building’s inherent tallness and flexibility. Wind induced displacements and vibrations become critical with increasing height. Excessive displacements can cause damage to partitions, cladding and interior finishes, whereas the human motion perception can induce concern regarding the structural safety and cause nausea and dizziness to the occupants. Analyzing and designing of buildings for static forces is a routine affair these days because of availability of affordable computers and specialized programs which can be used for the analysis. Stiffness and ductility considerations rather than strength would govern the design. The intent in seismic design then is to limit building movements, not so much to reduce perception of motion but to maintain the building’s stability and prevent danger to pedestrians due to breakage and falling down of nonstructural elements. In this thesis G+30, G+50, G+70 storied regular building modal has been analyzed by static & dynamic analysis. This building has the plan area of 42.30 m x 18.05 m with a storey height 3.0m and depth of foundation is 2.0 m. The static & dynamic analysis has been done on computer with the help of STAAD-Pro software using the parameters for the designing as per the IS-1893- 2002-Part-1 for the zone (V) and the post processing result obtained has been summarized in succeeding tables. In this study, structural systems that can be used for the lateral resistance of tall buildings are classified based on the basic reaction mechanism/structural behavior for resisting the lateral loads.